The impacts of herbivores and humans on the utilisation of woody resources in conserved versus non-conserved land in Maputaland, northern KwaZulu-Natal, South Africa - Van Rooyen, M.W. (Margaretha W.), 1950- (University of Pretoria, 2013)
Thesis (PhD (Wildlife Management))--University of Pretoria, 2008.